The High Time Resolution Universe Pulsar Survey – XV. Completion of the intermediate-latitude survey with the discovery and timing of 25 further pulsars. Issue 4 (11th February 2019) - Burgay, M; Stappers, B; Bailes, M; Barr, E D; Bates, S; Bhat, N D R; Burke-Spolaor, S; Cameron, A D; Champion, D J; Eatough, R P; Flynn, C M L; Jameson, A; et al.
ABSTRACT: We report on the latest six pulsars discovered through our standard pipeline in the intermediate-latitude region (| b | < 15°) of the Parkes High Time Resolution Universe Survey (HTRU). We also present timing solutions for the new discoveries and for 19 further pulsars for which only discovery parameters were previously published. Highlights of the presented sample include the isolated millisecond pulsar J1826−2415, the long-period binary pulsar J1837−0822 in a mildly eccentric 98-d orbit with a >0.27 M⊙ companion, and the nulling pulsar J1638−4233, detected only 10 per cent of the time. Other interesting objects are PSR J1757−1500, exhibiting sporadic mode changes, and PSR J1635−2616 showing one glitch over 6 yr. The new discoveries bring the total count of HTRU intermediate-latitude pulsars to 113, 25 per cent of which are recycled pulsars. This is the highest ratio of recycled over ordinary pulsars discoveries of all recent pulsar surveys in this region of the sky. Among HTRU recycled pulsars, four are isolated objects. Comparing the characteristics of Galactic fully recycled isolated MSPs with those of eclipsing binaries ('spiders'), from which the former are believed to have formed, we highlight a discrepancy in their spatial distribution. This may reflect a difference in the natal kick, hence, possibly, a different formation path. On the other hand, however, isolated fully recycled MSPs spin periods are, on average, longer than those of spiders, in line with what one would expect, from simple magnetic-dipole spin-down, if the former were indeed evolved from the latter.